Cartoon app on Android - Lee, Jason Zheng Hong (2015)
Social media such as Facebook has been developing quickly in the recent years. This has reached out to many people, who have decided to share their own pictures online while interacting with each other through the social media. In addition, the people nowadays have their own smartphones such as Android phone, which they could use to connect to the social media by the Internet. If they could change their online profile from real photo to cartoon-like photo, it could create a trend and a topic which people could chat about. This FYP project, Cartoon App an Android, aims to create a cartoon Android application which can convert real image into cartoon image through the means of filters, color quantization methods and edge drawing. It could also extend to turn real scenery image into cartoon form. After developing the application, it is able to select real image from camera or stored images from the smartphone and create cartoon image from the combined use of filters and quantization. Therefore, the application has met the main objectives of the FYP project. Furthermore, it is able to cartoonize the scenery as well , which is the extension of the FYP project. The users can also save the images into their android phone, so that it may be uploaded with online tools from social networking service like Facebook.